Иммуноцитогенетическая характеристика детей, страдающих сахарным диабетом I типа - Ковалева, В.И.; Будрейко, Е.А.; Чумак, С.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. The purpose of our study was to assess associative ability of acrocentric chromosomes (AC) in the peripheral blood lymphocytes of patients with type I diabetes mellitus. Methods. The analysis technique was performed according to the standard semimicromethod. Associations of acrocentric chromosomes (AAC) were assessed using D. Lang and E. Back (1968) criteria. Results. The results obtained have demonstrated that the number of activated T- lymphocytes with two AAC in children, suffering from type I diabetes, is 11.70 %, whereas in the population control this finding comes to 35.0 %. The average number of AAC per one cell in our patients was 2.19 less frequent than that in healthy age-matched persons and amounted to1.81 vs.3.97. Conclusions. The findings of our study indicate a lower associative ability of AC in probands with type I diabetes, which allows our authors to refer them to the persons with secondary immunodeficiency.

Key words: type I diabetes mellitus, children, acrocentric chromosomes, associations.